Pengaruh Kinerja Keuangan Perusahaan Terhadap Devidend Payout Ratio - Iwan Firdaus; Gean Karlos Purba (Jurnal Ekonomi, 2019)
This research was conducted to examine the effect of the current ratio (CR), Return on asset (ROA), Debt to Equity Ratio (DER) and Sales Growth to Dividend Payout Ratio (DPR). The object of this research is the pharmaceutical and cosmetics sub-sector listed on the Indonesia Stock Exchange in the period 2012-2016. This research was conducted using quantitative methods with a total of 30 samples of research were determined by saturated sampling. Method of hypothesis testing using t-test. This research uses the Current ratio (X1), Return on asset (X2), Debt to Equity Ratio (X3), Sales Growth (X4) as an independent variable and Dividend Payout Ratio as the dependent variable. The results of this research are Return on asset positive and have a significant effect on Dividend Payout Ratio, for Current ratios and Sales Growth a positive but significant effect on Dividend Payout Ratio, while the Debt to Equity Ratio positive and has no significant effect on Dividend Payout Ratio.